Bentuk dan Makna Pada Interior Gereja Katolik Regina Caeli di Pantai Indah Kapuk, Jakarta Utara - Puspitasari, Laurensia Ineke (Intra, 2016)
On June 11, 2006, the Catholic Church officially establish the Regina Caeli Church that appears in modern design, in contrast to the general Catholic Church which is often depicted in a classical style. The Catholic Church is loaded with the use of symbols. This study examines the form and meaning of Saint Regina Caeli Catholic’ Church in Pantai Indah Kapuk, North Jakarta. The method used in this research is a qualitative research method, using descriptive analysis methods. Data collected by literature studies, observations and interviews. The results showed that each of forms that exist on every element in this church have aesthetic significance that create an atmosphere to users towards the image of the church as the House of God.